Anderson-type polyoxometalate-based hybrid with high flame retardant efficiency for the preparation of multifunctional epoxy resin nanocomposites. (1st April 2020) - Peng, Chaohua; Chen, Ting; Zeng, Birong; Chen, Guorong; Yuan, Conghui; Xu, Yiting; Dai, Lizong
Abstract: Transition metal oxides based catalytic carbonization have been proved to be a promising way to enhance polymer flame retardancy, but finding better way to introduce organic phosphorus and transition metal oxide hybrids into polymer matrix to form nanocomposites is still a great challenge. In this work, an organic phosphorus and metal oxide hybrid compound named P–MnMo6 was prepared through combining 9, 10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide (DOPO) with polyoxometalate (POM). The as-prepared P–MnMo6 had a center of [MnMo6 O18 ] 3- and was used as the precursor of transition metal oxides to improve the flame retardancy of epoxy resin (EP). With the aid of the organic modification, the addition of P–MnMo6 not only maintained the transparency of EP but also enhanced the dynamic mechanical properties. Notably, the thermogravimetric analysis showed that the char yield of EP/P–MnMo6 composite increased significantly. Besides, epoxy with 8 wt% addition of P–MnMo6 passed the vertical burning grade (UL-94) V-0 rating with the limiting oxygen index (LOI) value of 30.4%. Cone calorimeter test indicated the peak heat release rate of EP/P–MnMo6 -4 decreased by 41%. Meanwhile, smoke products and CO were greatly suppressed. In addition, the potential flame retardancy mechanism of P–MnMo6 in epoxy matrix was proposed.